Value of Magnifying Chromoendoscopy and Magnifying Optical Enhancement Technology in Classifying Colorectal Polyps: A Prospective Controlled Study - Ying-Hao Song; Ruo-Xin Xu; Yong Zhang; Meng-Xuan Xing; Li-Dong Xu; Kun-Kun Li; Xing-Guo Xiao; Lu Li; Yan-Jing Xiao; Yu-Lei Qu; Ying-Jie Ma; Bao-Hui Jia; et al. (Gastroenterology Research and Practice)
Background and Aims. Magnifying chromoendoscopy (ME-CE) through the observation of pit patterns is a productive way to distinguish between neoplastic and nonneoplastic polyps. Magnifying optical enhancement technology (ME-OE) is an emerging virtual chromoendoscopy imaging technology and appeared to be a promising approach. However, this information is currently not available. This study is aimed at comparing the differential diagnostic value of ME-CE and OE for neoplastic and nonneoplastic polyps. Patients and Methods. Consecutive patients undergoing colonoscopy were randomized (1 : 1) into examination by ME-OE or ME-CE. Histopathological findings were utilized as the reference standard. Accuracy, sensitivity, specificity, and positive and negative predictive values of two endoscopy methods were compared using ME-OE (were classified according to the JNET classification) and ME-CE (were classified according to the Kudo pit pattern classification), respectively, and the time to predict the histological polyp type was compared. And the agreements between the pathological and clinical diagnosis by ME-OE or ME-CE were analyzed. Results. A total of 365 polyps were found in the 220 patients included (ME-OE: 185; ME-CE: 180.202 had nonneoplastic polyps, 163 had neoplastic polyps). The diagnostic accuracy of ME-OE was higher than that of ME-CE (93% vs. 92%, p>0.05). The average diagnosis time was lower in ME-OE than ME-CE (83±26.4 s vs. 194±17.7 s, p<0.001). The agreements between the pathological and clinical diagnosis were at least substantial in both groups. Conclusion. ME-OE was superlative to ME-CE in predicting the histology of polyps. OE devoted classification would possibly similarly enhance the endoscopist performance. The trial is registered with ChiCT2000032075.